DEVELOPMENT OF METHODOLOGY FOR DIGITAL MANAGEMENT BY SOCIO-ECONOMIC ORGANIZATIONS - A. Raychenko (Вестник университета, 2018)
The approaches, principles, designs serve as methodological basis of scientific research, professional activity and managerial education. Its application in the modern socioeconomic organization increasingly takes into account the possibilities of introducing digital technologies. On their basis an ever-increasing volume of managerial influences is carried out. The development of the methodology of digital management reveals the potential for operational impact, forms innovative activity, ensures the development of innovative opportunities. Application of developments in the methodology of digital management of socio-economic organizations ensures the development and use of substantially more accurate and operational resources for setting and achieving impact targets. The methodology of digital management is increasingly becoming a universal basis for the development and application of the necessary economy, innovative opportunities for advanced development.